2016
DOI: 10.1002/2015jc011402
|View full text |Cite
|
Sign up to set email alerts
|

An oceanic heat transport pathway to the Amundsen Sea Embayment

Abstract: The Amundsen Sea Embayment (ASE) on the West Antarctic coastline has been identified as a region of accelerated glacial melting. A Southern Ocean State Estimate (SOSE) is analyzed over the 2005–2010 time period in the Amundsen Sea region. The SOSE oceanic heat budget reveals that the contribution of parameterized small‐scale mixing to the heat content of the ASE waters is small compared to advection and local air‐sea heat flux, both of which contribute significantly to the heat content of the ASE waters. Above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
(68 reference statements)
2
27
0
Order By: Relevance
“…Recent observations as well as idealized modeling studies reveal that the thermocline depth or thickness of WW is important for controlling the PIG melt rate [ Dutrieux et al ., ]. Despite the possible importance of WW thickness on ice shelf melting, previous modeling studies in this region have focused primarily on CDW intrusion and have evaluated their simulations based only on bottom or deep CDW properties [e.g., Thoma et al ., ; Holland et al ., ; Schodlok et al ., ; Assmann et al ., ; Nakayama et al ., ; St‐Laurent et al ., ; Rodriguez et al ., ]. As a result, none of these models have shown a good representation of WW in the AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations as well as idealized modeling studies reveal that the thermocline depth or thickness of WW is important for controlling the PIG melt rate [ Dutrieux et al ., ]. Despite the possible importance of WW thickness on ice shelf melting, previous modeling studies in this region have focused primarily on CDW intrusion and have evaluated their simulations based only on bottom or deep CDW properties [e.g., Thoma et al ., ; Holland et al ., ; Schodlok et al ., ; Assmann et al ., ; Nakayama et al ., ; St‐Laurent et al ., ; Rodriguez et al ., ]. As a result, none of these models have shown a good representation of WW in the AS.…”
Section: Discussionmentioning
confidence: 99%
“…Initial model parameters of the baseline simulation are shown in Table . The baseline simulation resulted in WW that was too saline relative to observations (not shown, similar to Figures a and b), similar to previous studies [e.g., St‐Laurent et al ., ; Rodriguez et al ., ]. In order to achieve a better representation of WW and CDW, many forward simulations were conducted with different sets of model parameters and we used a combination of trial‐and‐error adjustments and a Green's function approach [ Menemenlis et al ., ] to optimize the simulation.…”
Section: Description and Adjustment Of Optimized Simulationmentioning
confidence: 99%
“…Combined with the incoming 0.96 TW crossing the 1,000‐m isobath, there is a total 1.64 TW of advective heat convergence within the Amundsen Sea segment (in the 1959–2009 mean). Rodriguez et al () find a 2005–2009 average total heat transport convergence of 1.15 TW in the Amundsen segment (their Table 2) in the coarser (1/6 ∘ ) Southern Ocean State Estimate. This is comparable to the 1.78 TW in the 2005–2009 POP average (not shown).…”
Section: The Cross‐shelf Break Heat Transport Along the Antarctic Conmentioning
confidence: 98%
“…In this model, even though the CDW exchange is not wind-driven, it is ultimately still sensitive to the wind. Rodriguez et al (2016) used the 1/6° resolution Southern Ocean State Estimate (SOSE; Mazloff et al, 2010) to examine cross-shelf exchange. Because SOSE is an assimilating model, its estimates of the transport across the Antarctic continental shelf are constrained by open ocean observations, including satellite altimetry as well as conductivity-temperature-depth profiles collected by elephant seals and Argo floats, but in its current configuration, it does not fully resolve processes on the continental shelf or in subglacial cavities.…”
Section: How Do Acc Waters Influence Subglacial Cavities?mentioning
confidence: 99%
“…Because SOSE is an assimilating model, its estimates of the transport across the Antarctic continental shelf are constrained by open ocean observations, including satellite altimetry as well as conductivity-temperature-depth profiles collected by elephant seals and Argo floats, but in its current configuration, it does not fully resolve processes on the continental shelf or in subglacial cavities. In SOSE for the Amundsen Sea just west of Drake Passage, Rodriguez et al (2016) showed that wind-stress curl, more than wind stress, governs variations in transport across the continental shelf into the Amundsen Sea.…”
Section: How Do Acc Waters Influence Subglacial Cavities?mentioning
confidence: 99%